Cross-cultural differences in visual perception - Čeněk, Jiří; Čeněk, Šašinka (Journal of Education Culture and Society, 2020)
According to recent cross-cultural studies there exist culturally based differences between visual perception and the related cognitive processes (attention, memory). According to current research, East Asians and Westerners percieve and think about the world in very different ways. Westerners are inclined to attend to some focal object (a salient object within a perception field that is relatively big in size, fast moving, colourful) focusing on and analyzing its attributes. East Asians on the other hand are more likely to attend to a broad perceptual field, noticing relationships and changes. In this paper we want to describe the recent findings in the field and propose some directions for future research.